The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000366063
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species-Mediated Endoplasmic Reticulum Stress in Contrast-Induced Renal Tubular Cell Apoptosis

Abstract: Background: Renal tubular cell apoptosis is a key mechanism of contrast-induced acute kidney injury. It has been reported that endoplasmic reticulum (ER) stress is the underlying mechanism of high osmolar contrast-induced renal tubular cell apoptosis. Whether ER stress is involved in low osmolar contrast-induced renal tubular cell injury remains unclear. In the present study, the roles of ER stress in iopromide-induced (a low osmolar contrast) renal tubular cell apoptosis and the effects of N-acetylcysteine (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…N-acetylcysteine also attenuated osmolar contrast-induced apoptosis of renal tubular cells by decreasing ROS levels and ER stress [31]. Similarly, flavonoids such as baicalin and quescetin reduced ER and oxidative stress, and they also ameliorated ischemia-reperfusion injury [32] or asymmetric dimethylarginine-induced apoptosis in glomerular endothelial cells [33].…”
Section: Antioxidative Chemicals and Proteins Relieve Endoplasmic Retmentioning
confidence: 93%
“…N-acetylcysteine also attenuated osmolar contrast-induced apoptosis of renal tubular cells by decreasing ROS levels and ER stress [31]. Similarly, flavonoids such as baicalin and quescetin reduced ER and oxidative stress, and they also ameliorated ischemia-reperfusion injury [32] or asymmetric dimethylarginine-induced apoptosis in glomerular endothelial cells [33].…”
Section: Antioxidative Chemicals and Proteins Relieve Endoplasmic Retmentioning
confidence: 93%
“…There are concerns about its nephrotoxicity in administration (Golshahi et al, 2014). Contrast-induced nephropathy (CIN) is the third leading cause of hospitalacquired acute renal failure accounting for 10-12% of all causes of hospital-acquired renal failure (Yang et al, 2014). It causes a prolonged in-hospital stay and predicting a bad recovery (Hou et al, 1983;Briguori et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…N-Acetyl-Lcysteine (NAC), a potent antioxidant, was used to alleviate ATO-induced ROS and the resulting oxidative DNA damage. Other reports and our previous studies demonstrated that 10 mM NAC is sufficient to reduce ROS level in various cell lines without affecting cell growth (Gu et al, 2015;Yang et al, 2014). Therefore, in this study, this NAC dosage was used and the results showed that it did not affect HepG2 cell growth (data not shown).…”
Section: Ros-mediated Dna Damage Was Responsible For the Ato-induced mentioning
confidence: 63%